Pengajaran Subject – Verb Agreement bagi Mahasiswa Program Studi Bahasa dan Sastra Indonesia - Hasriani G Hasriani G; Maemuna Muhayyang; Mardiyanah Nasta; Rahmad Risan (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
This study aims to depict the ability of secondsemester students of Indonesian and Literature Study Programin Faculty of Language and Literature in Universitas NegeriMakassar regarding the subject-verb agreement in English andthe ability to make sentences in English correctly both spokenor written. The methods employed in this study werepresentation and training. The majority of the participants(90%) are able to apply their knowledge and understanding,express present tense sentences properly and correctly both inspoken and written and 10% of them still make errors.Participants activeness is indicated by their positive attitude,motivation, confidence, and responsibility in practicing anddoing their tasks, which support their knowledge andunderstanding in subject-verb agreement materials. Based onthe observations and evaluation, each assignment given to thetraining participants had a significant impact on theirknowledge and understanding of the suitability between thesubject and the predicate in English sentence structure.